Transmit diversity via oscillating-beam-pattern adaptive antennas an evaluation using geometric-based stochastic circular-scenario channel modeling. - Zekavat, S.A (IEEE Transactions on wireless communications)
Applying carefully-selected time-varying phases (delays) to array elements of an adaptive antenna, the beam pattern oscillates in a controlled manner. This creates a time varying channel with a controllable coherence time. With an adaptive antenna at the base station (BS) and a single omnidirectional antenna at the mobile, the controllable coherence time is used by the mobile to exploit time diversity and enhance performance. In this work, assuming an oscillating-beam-pattern antenna array at the BS, the channel is properly modeled and the coherence time is evaluated. A so-called geometric-based stochastic channel model is presented, assuming a circular coverage area, and the channel is simulated in an urban environment. We demonstrate the relationship between coherence time and the antenna array control parameters and show that seven-fold-diversity can be created via small beam pattern oscillation.